Spark-Plasma Sintering and Related Field-Assisted Powder Consolidation Technologies - Eugene A. Olevsky (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Electromagnetic field-assisted sintering techniques have increasingly attracted attention of scientists and technologists. Spark-plasma sintering (SPS) and other field-assisted powder consolidation approaches provide remarkable capabilities to the processing of materials into configurations previously unattainable. Of particular significance is the possibility of using very fast heating rates, which, coupled with the field-assisted mass transport, stand behind the purported ability to achieve high densities during consolidation and to maintain the nanostructure of consolidated materials via these techniques. Potentially, SPS and related technologies have many significant advantages over the conventional powder processing methods, including the lower process temperature, the shorter holding time, dramatically improved properties of sintered products, low manufacturing costs, and environmental friendliness.